1986
DOI: 10.7557/2.6.2.641
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of the Kaminuriak caribou herd, 1968 - 1985

Abstract: The Kaminuraik caribou herd apparently declined from about 120 000 animals in 1950 to 63 000 in 1968. Beginning in 1968 documentation of herd trend was based on the estimate of the number of breeding (pregnant and post-partum) females on the calving ground during the birth peak. It appeared as if we understood the basic population processes responsible for the decline when we correctly predicted a drop from 14 800 breeding females in 1977 to 13 000 in 1980. However a three-fold increase, to 41 000 breeding fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 4 publications
2
25
0
Order By: Relevance
“…Over-winter calf mortality can be high (Heard & Calef, 1986), however Bergerud (1971) found no evidence that calves died during winter at a higher rate than adults. Over-winter mortality of calves from the Delta herd was relatively low and no higher than cohorts >24 months (Davis et al, 1988;.…”
Section: Sex and Age Compositionmentioning
confidence: 99%
“…Over-winter calf mortality can be high (Heard & Calef, 1986), however Bergerud (1971) found no evidence that calves died during winter at a higher rate than adults. Over-winter mortality of calves from the Delta herd was relatively low and no higher than cohorts >24 months (Davis et al, 1988;.…”
Section: Sex and Age Compositionmentioning
confidence: 99%
“…Barren-ground caribou show a density-dependent mechanism where range expansion and contraction is a function of the size of the herd (Simmons et al 1979, Bergerud et al 1984, Heard and Calef 1986, Messier et al 1988, Couturier et al 1990). Such dynamics may influence the distribution o f wolves (Heard and Williams 1992).…”
Section: Descriptive Analysesmentioning
confidence: 99%
“…The distribution of barren-ground caribou is density-dependent such that range expansion and contraction are a function of the size of the herd (Simmons et al 1979, Bergerud et al 1984, Heard and Calef 1986, Messier et al 1988, Couturier et al 1990, Gunn et al 2012. Gunn et al (2013) reported that the winter range of the Bathurst herd has contracted since 2002, corresponding to the decline of the herd.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations